135k views
25 votes
Solve 8x – 5 = 23 + 4x.

User Farhadix
by
5.0k points

2 Answers

5 votes

Answer:

7

Explanation:

First you want to simplify the equation

8x + (-5) = 23 + 4x

-5 + 8x = 23 + 4x

Then solve for x, but before we do that we !!!must!!! move all terms that have x to the left. Everything else would go to the right.

So we add -4x to both sides ..

-5+ 8x + (-4x) = 23 + 4x + (-4x)

-5 + 4x = 23 + 4x + (-4x)

-5 + 4x = 23 +0

-5 + 4x = 23

Then add 5 to both sides of the equation:

-5 + 5 + 4x = 23 + 5

0 + 4x = 23 + 5

4x = 23 + 5

4x = 28

Then divide each side by 4:

x = 7

And there you have it. The answer is 7. Hope this helps! :)

User Borichellow
by
5.5k points
10 votes

Answer: X equals 7

Explanation:

User Georger
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.